Does Renal Mass with Venous Thrombosis always Indicate Renal Cell Carcinoma? A Case Series - Ghorbani, Hamidreza; Farzadnia, Mehdi; Golshan, Alireza (Urology Journal, 2022)
Intravascular tumor extension in the major renal veins or their tributaries, as a rare but important clinical entity that can change the disease stage, prognosis, and approach to treatment. There is limited literature on the obstruction of renal vein and IVC by tumor thrombus in other types of renal tumors that are not of RCC type. We presented four different renal tumor cases with the presence of gross renal vein or IVC thrombosis. Although the incidence of renal vein and IVC tumor thrombus might be suggestive of (often diagnosed as) RCC, the possibility of other non-RCC renal tumors should be included in the differential diagnosis.